Spectrally Stable Ultra‐Pure Blue Perovskite Light‐Emitting Diodes Boosted by Square‐Wave Alternating Voltage. Issue 2 (25th October 2019) - Tan, Zhifang; Luo, Jiajun; Yang, Longbo; Li, Xiao; Deng, Zhiyang; Gao, Liang; Chen, Hongting; Li, Jinghui; Du, Peipei; Niu, Guangda; Tang, Jiang
Abstract: Perovskite light‐emitting diodes (PeLEDs) have attracted great research interests considering their excellent luminescent properties and solution processability. Despite rapid advances of green‐, red‐, and near‐infrared‐emitting PeLEDs, blue‐PeLEDs, as an essential part for full‐color display and solid‐state lighting, still remain challenging due to their low efficiency and spectral instability. Here, reported are spectrally stable blue‐PeLEDs biased by an alternating voltage. First, 2‐phenoxyethylamine‐passivated CsPbBr x Cl3− x is obtained as a blue emitter with a record photoluminescence quantum yield of 88%. Subsequently, constructed and optimized are pure blue‐emitting PeLEDs exhibiting electroluminescence (EL) at 468 nm with a high external quantum efficiency of 0.71%. Furthermore, driven are the devices by square‐wave alternating voltage and stabilized are the EL spectra for 12 h by suppressing the detrimental halide migration during operation. It is believed that this work provides an alternative way for the spectrally stable mixed halide blue PeLEDs. Abstract : Based on mixed halide perovskites, a pure blue film with a photoluminescence quantum yield of 88% is obtained. Corresponding blue perovskite light‐emitting diode (LED) exhibits electroluminescence (EL) at 468 nm with an external quantum efficiency of 0.71%. By introducing the square‐wave alternate voltage for driving LED device, the EL spectrum of the device shows negligible shifts for 12 h.